2020
DOI: 10.3390/su12229754
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Soil Quality Index for Soils under Different Agricultural Management Conditions in the Central Lowlands of Mexico: Physicochemical, Biological and Ecophysiological Indicators

Abstract: The Bajío—Mexico’s central lowlands—is a region of economic importance because of its agricultural industry. Over time, agricultural practices have led to soil deterioration, loss of fertility, and abandonment. In this study, six agricultural soils were analyzed: AGQ, CTH, CTJ, JRM, CRC, and CYI, and used to develop a soil quality index (SQI) that includes the use of physicochemical, biological, and ecophysiological indicators to differentiate soil quality. Principal component analysis (PCA) was used, reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The spatial trend of soil quality increases from north to east and this trend is consistent with current conditions, as low soil quality in the north may be due to a high percentage of calcium carbonate, a high percentage of sodium exchangeable, high salinity, and low concentration of organic matter and intensive mismanagement practices in agriculture [47] have shown that organic matter, clay, EC, and CEC are the most influential factors in the determination of SQI, confirming the importance of using these parameters in the current study. Developing soil quality classes can minimize agricultural management costs, such as improving soil quality for a slightly moderate class, which may need improvement compared to low-quality soils, and two types of soils need improvement.…”
Section: Sqi Using Geospatial Techniquessupporting
confidence: 74%
“…The spatial trend of soil quality increases from north to east and this trend is consistent with current conditions, as low soil quality in the north may be due to a high percentage of calcium carbonate, a high percentage of sodium exchangeable, high salinity, and low concentration of organic matter and intensive mismanagement practices in agriculture [47] have shown that organic matter, clay, EC, and CEC are the most influential factors in the determination of SQI, confirming the importance of using these parameters in the current study. Developing soil quality classes can minimize agricultural management costs, such as improving soil quality for a slightly moderate class, which may need improvement compared to low-quality soils, and two types of soils need improvement.…”
Section: Sqi Using Geospatial Techniquessupporting
confidence: 74%
“…Differences in plant species did not significantly change soil pH (Table 1). Meanwhile, the roots may have secreted weak organic acid ions, sugars, amino acids, vitamins, and inorganic ions (HCO 3 − , OH − , and H + ), all of which might alter soil pH (Bedolla-rivera et al, 2020). Untreated soil had the highest CaCl 2 extractability (Cu 100 and Cd 0.15 mg kg −1 in 2015) (Table 1).…”
Section: Soil Chemical Characteristics and Metal Availabilitymentioning
confidence: 99%
“…Table 8 is the result of the correlation analysis between soil quality variables. The correlation results show the average correlation value < 0.5, so the relationship between variables is insignificant (Bedolla-Rivera et al, 2020). Two associations have a correlation value > 0.5, namely (1) pH sand and clay;…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 94%
“…The limiting factors are the availability of P and soil texture. These two properties can be improved by adding organic matter rich in P and physically improving soil texture (Bedolla-Rivera et al, 2020). Nutrient P includes slow-release nutrients from organic and inorganic fertilizers (Szulc et al, 2020).…”
Section: Assessment Of Soil Quality Index (Sqi)mentioning
confidence: 99%